2013
DOI: 10.1523/jneurosci.2675-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Saccade Modulation by Optical and Electrical Stimulation in the Macaque Frontal Eye Field

Abstract: Recent studies have demonstrated that strong neural modulations can be evoked with optogenetic stimulation in macaque motor cortex without observing any evoked movements (Han et al., 2009, 2011; Diester et al., 2011). It remains unclear why such perturbations do not generate movements and if conditions exist under which they may evoke movements. In this study, we examine the effects of five optogenetic constructs in the macaque frontal eye field and use electrical microstimulation to assess whether optical per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
119
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(132 citation statements)
references
References 36 publications
6
119
2
1
Order By: Relevance
“…First, although earlier primate optogenetics studies reported significant firing rate changes in only 38-68% of neurons, all within 400 μm to 1 mm of the light source (14,18,19), we found inactivation (>80% firing reduction) over a volume (>10 mm 3 ) comparable to the inactivated tissue volumes in cooling (1) and pharmacological inactivation studies (2,3,7,72), which silence 80-100% of neurons to <80% of baseline over 4.2-14 mm 3 . Second, in contrast with previous studies of inhibitory opsins in primate cortex (14,18,19), which report a subpopulation (∼10-25% of the total cells) that increases its firing rate during illumination (14,18,19) and potentially cancels the effects of inhibition on behavior, not a single neuron in this study increased its firing rate in response to illumination. Optogenetics studies of excitatory opsins have reported similar heterogeneity (17).…”
Section: Discussioncontrasting
confidence: 59%
See 4 more Smart Citations
“…First, although earlier primate optogenetics studies reported significant firing rate changes in only 38-68% of neurons, all within 400 μm to 1 mm of the light source (14,18,19), we found inactivation (>80% firing reduction) over a volume (>10 mm 3 ) comparable to the inactivated tissue volumes in cooling (1) and pharmacological inactivation studies (2,3,7,72), which silence 80-100% of neurons to <80% of baseline over 4.2-14 mm 3 . Second, in contrast with previous studies of inhibitory opsins in primate cortex (14,18,19), which report a subpopulation (∼10-25% of the total cells) that increases its firing rate during illumination (14,18,19) and potentially cancels the effects of inhibition on behavior, not a single neuron in this study increased its firing rate in response to illumination. Optogenetics studies of excitatory opsins have reported similar heterogeneity (17).…”
Section: Discussioncontrasting
confidence: 59%
“…The maximum total light power density applied in this study was 100 mW/mm 2 , similar to what was used in the first electrophysiological demonstrations of optogenetics in the primate (19,61), as well as to what has been used for optogenetic modulation of superficial cortical neurons through a window on the brain (62,63). However, it is much lower than subsequent primate studies that reported behavioral changes using maximal light power densities ranging from several hundred milliwatts per square millimeter to >10 W/mm 2 (11)(12)(13)(14)(15)49).…”
Section: Significancementioning
confidence: 57%
See 3 more Smart Citations